Cloud-Native Coastal Turbid Zone Detection Using Multi-Temporal Sentinel-2 Data on Google Earth Engine - Pertiwi, Avi Putri; Lee, Chengfa Benjamin; Traganos, Dimosthenis (Frontiers in Marine Science, 2021)
The lack of clarity in turbid coastal waters interferes with light attenuation and hinders remotely-sensed studies in aquatic ecology such as benthic habitat mapping and bathymetry estimation. Although turbid water column corrections can be applied on regions with seasonal turbidity by performing multi-temporal analysis, different approaches are needed in regions where the water is constantly turbid or only exhibits subtle turbidity variations through time. This study aims to detect these turbid zones in optically shallow coastal waters using multi-temporal Sentinel-2 surface reflectance datasets to improve the aforementioned studies. The herein framework can be paired with other aquatic ecology remote sensing studies to establish the clear water focus area and can also be used by decision makers to identify rehabilitation areas. We selected the coastlines of Guinea-Bissau, Tunisia, and west Madagascar as our case studies which feature wide-ranging turbidity intensities across tropical, subtropical, and Mediterranean waters and applied three different methods for the turbid zone detection: Otsu’s method for bimodal thresholding, linear spectral unmixing, and Random Forest machine learning method on Google Earth Engine as an end-to-end process. Based on our experiments, the Random Forest method yields good results in all study regions with overall accuracies ranging between 88-96% and F1-scores between 0.87-0.96. Turbid zone detection is highly site-specific due to the inter-class variability that is mainly affected by the nature of the suspended materials and the environmental characteristics of the site.